Validity and reliablity of the Persian health-promoting lifestyle profile II questionnaire - Teamur Aghamolaei; Amin Ghanbarnejad (Gonabad University of Medical Sciences, 2015)
Health promoting behavior is one of the important health characteristics and well known as disease preventing factor. The aim of this study was assessment of reliability, validity and factor structure of Health Promoting Lifestyle Profile II (HPLP II) using confirmatory factor analysis (CFA). This cross sectional study was done among 706 persons over 15 years old in Bandar Abbas through cluster sampling. Data was analyzed using confirmatory factor analysis (CFA), Cronbach's α coefficient and inter scale correlation. Based on CFA, with omission three items from original HPLP II questionnaire, revised 49-items Farsi questionnaire had good fit. Goodness of fit index was 0.93. Cronbach's α for total questionnaire was 0.92 and ranged from 0.71 to 0.86 for subscales. Inter scale correlation was significant and varied from 0.44 to 0.89. According to results, revised 49-items Farsi version of HPLP II questionnaire was introduced as a valid and reliable tool for assessing health promoting behaviors.